Impact of a Proposed Barrage on the Tidal Wave Characteristics and Salinity Distribution in the Shatt Al-Arab River Estuary - Lafta , Ali A.; Abdullah, Sadiq S. (Mesopotamian Journal of Marine Sciences, 2024)
The response of the tidal hydrodynamics and salinity status in the Shatt Al-Arab river estuary (SARE) to the installation of a barrage was investigated using Mike11. The results demonstrated that installing a barrage might cause many changes in the hydrodynamic behavior of SARE. The most noticeable alteration occurs in the tidal range, particularly near the barrage location, where there are significant increases in tidal range in such regions. However tidal range variations are intimately correlated with tidal constituents amplitude variations, particularly in the vicinity of the barrage site where the largest amplitude variation of the tidal components occurs. To examine the variations in the tidal constituent characteristics, six stations were chosen . In the first three stations, there was a significant increase in the amplitudes of the semi-diurnal components, namely M2, S2, and N2, whereas in the other stations, there was a slight decrease. Conversely, the diurnal constituents amplitudes exhibit a notable increase in the first five stations but remain unchanged in the sixth. Furthermore, there are noticeable variations in the phase of the tidal components, with the most significant change occurring between stations five and six. Additionally, several scenarios were performed to determine the appropriate freshwater inflow from the Karun river to maintain the SARE environment. Based on the results, it appears that freshwater flows of 70, 80, 90, and 100 m3/sec may be suitable to sustain the SARE environment, as long as the length of the salinity incursion remains below 60 km.